FACING REALITY: A NEED TO CHANGE THE LEGAL FRAMEWORK OF THE EU PUBLIC HEALTH POLICY AND THE INFLUENCE OF THE PANDEMIC OF COVID-19 ON THE PERCEPTION OF IDENTITY AND THE ROLE OF THE EU (EU and comparative law issues and challenges series (ECLIC), 2022)
The main aim of this article is to highlight two interconnected issues raised in the context of the COVID-19 pandemic. The first one concerns a need to change the EU Health Policy legal framework, particularly the founding treaties (TEU and TFEU), while the second one relates to the issue of the very perception of the identity of the European Union. The possible adequate solution for the situation created by the unprecedented nature of the COVID-19 pandemic and unprecedented measures that followed, was to proclaim state of emergency, which was largely avoided. It seems that it should be considered whether there is a need for amendments of the European Union founding treaties and/or the Charter on Fundamental Rights by providing the possibility of the state of emergency proclamation in the case of “the threats of the life” of the EU. The European Union is not entrusted with the competencies, powers, and responsibilities in health matters such as a pandemic, however founding treaties, functioning institutions as well as procedures seem sufficient for an effective response to health crises such as the one caused by the COVID-19 pandemic. However, having in mind experience with the COVID-19 pandemic it seems that there is a need to strengthen the EU legal framework concerning the issues of pandemic and similar threats, not by altering the nature of the EU competence regarding health issues, but by identifying the threats such as pandemic in the founding treaties that should contain basic regulations concerning European Centre for Disease Prevention and Control. In that manner the efficient response would be in a form of an institutionalized mechanism at the core of the European Union instead of being fully dependent on the variable political will. At the same time there is an urgent need to identify those Health Policy issues that should be an adequate subject of judicial scrutiny. The COVID-19 pandemic also proved that Member States and the European Union should be more realistic regarding the perception of the role and identity of the European Union. The author argues that the identity of the European Union is blurred with a variety of considerations and that its content and features should be more determined, not only in academic literature but also in political practice, especially when it comes to the issue of self-determination of the European Union. The world is not the same as it was before the pandemic, and it seems that the European Union, in order to be prepared to face new challenges, must build its identity in realistic parameters and act in one voice “if it wants to make itself heard and play its proper rôle in the world”, as it was declared in the 1973 Declaration on the European Identity.